2008
DOI: 10.1007/s11695-008-9442-x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound-Guided Gastric Botulinum Toxin Injections in Obese Subjects: A Pilot Study

Abstract: Background-Gastric injections of botulinum toxin A (BTA) may induce changes in gastric emptying and body weight, but results vary. BTA dose and depth of injection may affect efficacy. This study assessed changes in gastric emptying, satiation, symptoms, and body weight after endoscopic ultrasound (EUS)-guided injection of 100 or 300 U BTA into gastric antral muscularis propria of obese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 30 publications
(43 reference statements)
2
24
0
Order By: Relevance
“…In addition, this study found a prolonged gastric emptying time and reduced maximal gastric capacity for liquids [67]. Similar results have been found in an open label study of 10 obese adults who received 100 units (4 patients) or 300 units (6 patients) of BoNT-A and were followed for 16 weeks [68]. …”
Section: Clinical Studies Of Intragatsric Bont-a For Obesitysupporting
confidence: 76%
“…In addition, this study found a prolonged gastric emptying time and reduced maximal gastric capacity for liquids [67]. Similar results have been found in an open label study of 10 obese adults who received 100 units (4 patients) or 300 units (6 patients) of BoNT-A and were followed for 16 weeks [68]. …”
Section: Clinical Studies Of Intragatsric Bont-a For Obesitysupporting
confidence: 76%
“…Injections were performed via a 25 gauge EUS needle under real-time EUS guidance, targeting the gastric muscularis propria as previously described. 10 Three rings of injections were performed around the antral circumference, with 5 equally spaced 2 mL injections in each ring. The rings were 1 to 2 cm apart, and the most distal ring was 2 to 3 cm proximal to the pylorus.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Gastric antral injection of BOTOX appeared promising, as it also delayed gastric emptying and induced satiation in an open-label trial 62 ; however, in a 4-month trial, despite documentation of delay in gastric emptying, there was no significant reduction in body weight. 63 A recently published meta-analysis and meta-regression of 4 randomized, controlled trials evaluating antral BOTOX injection suggested overall benefit (Hedges’ g −0.521; 95% CI, −0.845 to −0.040, P = .031), but 3 of the 4 trials were individually nonsignificant.…”
Section: Novel Devices Proposed In Obesity Treatment and Their Potentmentioning
confidence: 96%